Satellite Glial Cells of the Dorsal Root Ganglion: A New “Guest/Physiopathological Target” in ALS - Ruiz-Soto, María; Riancho, Javier; Tapia, Olga; Lafarga, Miguel; Berciano, María T. (Frontiers in Aging Neuroscience, 2020)
Introduction: Amyotrophic lateral sclerosis (ALS) might not only be circumscribed to the motor system but also involves other neuronal systems including sensory abnormalities. In line with this notion, we aimed to assess the pathophysiology of sensory disturbances in the SOD1G93A mouse model of ALS, focusing on the satellite glial cells (SGCs) at the dorsal root ganglion (DRG) as a new potential target of the disease. Material and Methods: The presence of sensory disturbances was evaluated using von Frey, hot plate and hot water tail immersion tests at 75 days old, which represented the motor-pre-symptomatic stage. Cell biology analysis was performed at 75 and 95 days old and included conventional histology, immunofluorescence and electron microscopy of sensory neuron-SGC unit dissociates as a well as western blotting from DRG lysates. Results: At 75 days old, von Frey and hot plate tests demonstrated clear thermoalgesic disturbances in ALS transgenic mice. Histological studies of the SN-SGC units revealed abnormal SOD1 accumulation, which was associated with nitro-oxidative stress and biogenesis of lipid droplets in SGCs. Interestingly, these alterations led to a progressive lysosomal storage disorder and occasionally vacuolar degeneration in SGCs. Conclusions: SGCs emerge as a primary pathophysiological target in the SOD1 transgenic murine model of ALS, clearly reinforcing the pathogenic role of glial cells in motor neuron disease. Presymptomatic alterations of SGCs, might not only be responsible of sensory disturbances in ALS, but due to spinal cord sensory-motor circuits could also contribute to anterior horn motor disturbances